PRIMARY PREVENTION OF VERRUCA PLANTARIS THROUGH TOPICAL HERBAL AND VITAMIN DERIVATIVE - DO ACOFP, MARK KEVIN KAUFFMAN; ROTH-KAUFFMAN JD, MICHELE MARIE; KHURANA, PRATEEK; SINIBALDI, LORRIE; WALKOWSKI, AARON; APUGLIESE, ANDREW; ESSA, JUNAID (International Journal of Applied Pharmaceutics, 2021)
Objective: Verrucae plantaris (VP) results from environmental exposure to human papillomavirus causing plantar warts of the foot, resistant to treatment, and high recurrence rates. Current treatment paradigms focus on the treatment of lesions as opposed to primary prophylaxis. We hypothesize that a topical combination of herbal supplement with anti-viral properties and a vitamin derivative* can be used prophylactically to decrease the primary incidence. Methods: We initiated a double-blinded clinical study with participants (n=282) randomization into control (lotion emollient only) (n=120), treatment (herbal and vitamin derivative) (n=110) and no treatment (NT) (n=52). Participants underwent examination of the feet at baseline (0 months) to exclude VP lesions and were randomized to receive a bottle containing topical lotion with emollient only, control (C), lotion with an herbal and vitamin derivative, treatment (T), or NT, where participants did not apply anything to their feet. C and T participants applied lotion topically to the feet once daily and were examined at 3, 6, 9, and 12 months to document the incidence of VP. Results: No incidence of VP occurred in the T group (0/110=0% incidence), two lesions in the C group (2/120=1.7% incidence), and five lesions in the NT group (5/52=9.6% incidence). Conclusion: Treatments for VP rely on treating lesions after they occur, have high degrees of variability in success, risk of continued transmission during treatment, and have high rates of recurrence. Although the study number is relatively low, early indications show decreasing incidence of VP from 9.6% in participants with NT to 1.7% in participants who used lotion only, suggesting increased health of the plantar epidermis, and 0% incidence in those participants applying topical herbal and vitamin derivative*. Additional study with increased numbers of participants is warranted.